Biohyrogen production from agricultural waste by dark fermentation - Mismisuraya, Meor Ahmad; Noorulnajwa Diyana, Yaacob; Hafizah, Mohd Johar (Malaysian Invention and Design Society (MINDS), 2012)
Mismisuraya Meor Ahmad and her team from School of Bioprocess Engineering won bronze for Biohyrogen production from agricultural waste by dark fermentation. 23rd International Invention, Innovation and Technology Exhibition 2012 (ITEX 2012) organized by Malaysian Invention and Design Society (MINDS), 17th - 19th May 2012 at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur, Malaysia.